Strategi Peningkatan Daya Saing Produk Melalui Pelatihan Kemasan Produk pada Pelaku Usaha Perempuan di Desa Api-Api Wonokerto - Ali Imron; M.Iqbal Notoatmojo; Rizka Ariyanti (Lembaga Pengembangan Kinerja Dosen, 2024)
The partner in this PkM activity is the Api-Api village government, Wonokerto, Pekalongan district, this village is one of the villages that has several MSME groups or women entrepreneurs. The MSME aims to be a forum for innovation for women entrepreneurs to develop themselves as strong entrepreneurs. Based on a situation analysis of the main problems currently faced by partners in the marketing aspect and business management aspect. Marketing aspects include low competitiveness and business performance due to lack of innovation, weak branding, weak positioning and not optimal use of the internet in marketing. Meanwhile, aspects of business management include business management that is not yet professional, not having a business permit/PIRT and halal certification, conventional financial reporting. Based on these problems, through this activity, several solutions will be provided, especially product packaging problems so that they can attract consumers, namely strategies for preparing content, images, sentences and things that may or may not be included in the packaging regarding their impact on marketing. The method of implementing activities uses a participatory approach through training activities, with measurable achievement targets. Through this training activity, participants understand the material and are expected to implement the training results. As a monitoring aspect, the PkM team visits partners to see the implementation of the training provided.